Karakteristik Dan Tujuan Pendidikan Berbasis Entrepreneurship - Farihatul Hasanah; Lumanatul Latifah; Holilur Rahman (CV. ITTC INDONESIA, 2024)
Abstract Entrepreneurship education is given to students as early as possible considering the economic problems faced in this country. Entrepreneurship education is basically a process of internalizing entrepreneurship values to students so that they have the character of an entrepreneur. The value of entrepreneurship is important for students to face the problems of life, the purpose of this study is to determine the objectives and characteristics of entrepreneurship education. The research method used is library research with a descriptive approach. Data analysis techniques use data reduction, data presentation and conclusions. The results of this study state that entrepreneurship education aims to develop the attitude, spirit and ability to create something of value for oneself and others. there are five main values in entrepreneurship education, including the courage to take risks, be creative in facing problems and opportunities, have a leadership spirit, be task and result oriented and have strong motivation and drive to succeed.